Kadar Admixture Berbagai Jenis Superplasticizer Dan Karakteristik Mortar Grouting - Rizaldo Bagus Dinata; Arman Setiawan; Eka Yuniarto (Program Studi Teknik Sipil Universitas Bosowa, 2023)
In the world of construction, mortar has many functions, for example as an adhesive for precast concrete, filling voids in concrete and grouting materials. In this modern era, there are many additives that can be used to make mortar stronger and make it easier to manufacture. In this study, the additives used were Visco flow 3880 lv, Master gelnium 8305, and Consol flow 168. These additives able to slow down the drying process and can increase the strength of the mortar. This research is an experiment conducted at the Makassar Concrete Bosowa Laboratory. The composition of the mortar that will be used in this test is 1 kg of cement: 2 kg of sand. The dosage for each additive is 0.8%, 1%, and 1.2%. From the results of the study using a visco flow superplasticizer with a dose of 0.8%, 1%, and 1.2%, respectively, the results were 34.69 mpa, 35.10 mpa, 33.42 mpa. By using master glenium got 33.40 mpa, 34.20 mpa, 29.37 mpa. Meanwhile, using the console flow 30.80 mpa, 36.39 mpa, 36.10 mpa